Fe‐Doped p‐ZnO Nanostructures/n‐GaN Heterojunction for "Blue‐Free" Orange Light‐Emitting Diodes. Issue 17 (14th June 2017) - Zhao, Wanqiu; Xiong, Xing; Han, Yibo; Wen, Li; Zou, Zhengguang; Luo, Shijun; Li, Haixia; Su, Jun; Zhai, Tianyou; Gao, Yihua
Abstract : In order to obtain the necessary band gap for light‐emitting diodes (LEDs) with zero emission at blue wavelengths ("blue‐free"), quasi‐3D nanostructures of p‐type Fe‐doped zinc oxide (ZnO:Fe) are fabricated on an n‐type GaN substrate. The ZnO:Fe nanostructure comprises an array of vertical nanowires attached at the nodes of a 2D network. Elemental analysis and field‐effect‐transistor (FET) and current–voltage ( I – V ) measurements indicate the successful iron‐doping of ZnO. After doping, the ZnO exhibits p‐type conductivity, a local‐charge‐reservoir layer, and an abundance of Fe‐related deep levels. The cathodoluminescence (CL), photoluminescence (PL) at various temperatures (down to 4.65 K), and electroluminescence (EL) confirm the creation of Fe‐related donor and acceptor levels. New donor levels may be attributed to the substitution of Fe for some Zn sites ("FeZn "), while new acceptor levels may be due to the bind of FeZn with Zn vacancies, (producing FeZn –V Zn pairs). These doping‐induced energy levels are helpful in restricting the intrinsic ZnO UV and blue emission, and a stable blue‐free orange LED device is achieved. It has chromaticity coordinates of ∼(0.483, 0.447) and a color temperature of ∼2574 K under bias voltages of 6–16 V, making it potentially applicable to electronic display systems. Abstract : Zero emission at blue wavelengths is made possible in an orange light‐emitting diode comprising a p‐ZnO:Fe/n‐GaN heterojunction. The ZnO is Fe‐doped and has a quasi‐3D nanostructure, where 1D nanowires protrude out of the 'note' of 2D nanonetwork. The Fe‐doping enables p‐type conductivity, introduces an abundance of deep levels, and produces a local‐charge‐reservoir layer, all of which help to restrict the intrinsic blue/UV emission of ZnO.